HEPATOSOMATIK INDEKS DAN DIAMETER HEPATOSIT MENCIT (Mus musculus L.) BETINA SETELAH PAPARAN EKSTRAK ETANOL DAUN MIMBA (Azadirachta indica Juss.) - Anisa Nurul Hasana; Agung Janika Sitasiwi; Sri Isdadiyanto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Neem leaves is one part of the neem tree which can be used as a traditional medicinal herb. The purpose of this study was to examine the effect of neem leaf ethanol extract on hepatosomatic index (HSI) and hepatocyte diameter in female mice. The study used a Complete Randomized Design consist of 4 treatments and 5 replications including K (aquadest), P1, P2 and P3 (neem leaf ethanol extract with dose of 8.4,11.2 and 14 mg/ kg BW/day. The treatment was administered orally with a volume of 0.2 mL for 21 days. Body weight were measured every 7 days. The liver was isolated, weighed and histologically prepared with paraffin method, HE staining and 5 Î¼m incision thickness. HSI value determined from body weight and liver weight. Hepatocyte diameter were measured on 7 hepatocytes per lobule. The data was analyzed using ANOVA at 95% confidence level. The results showed that neem leaf ethanol extract had no significant effect (p> 0,05) on body weight, liver weight, HSI value and hepatocyte diameter, but the liver microanatomy showed hepatocyte damage. It can be concluded that exposure of neem leaf ethanol extract for 21 days still safe to be used for reference of traditional medicine. Keywords: Neem leaf, HSI, hepatocyte diameter